The Effects of Obesity on Joint Integrity and Mobility. A Cross-Sectional Anatomical Study - Muhammad Umar, Sitwat Amna, Sabahat Zulfiqar, Farhana Jafri, Muhammad Faisal Khan, Mushtaq Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Obesity is a major global health problem resulting in a great deal of musculoskeletal disorders, most prominently joint degeneration and impaired mobility. Aims and Objectives: This study aimed and objective to assess the effect of obesity on joint integrity and mobility in Pakistani adults using radiographic and functional assessment. Method: A cross-sectional study was conducted at different tertiary healthcare centres in Lahore, Pakistan, among n=150 participants (30–60 years). Nonobese (BMI < 25 kg/m², n=75) and obese (BMI ≥ 30 kg/m², n=75) were categorized as the participants. X-rays and MRI were used to assess joint integrity (joint space narrowing, osteophyte formation, and subchondral sclerosis). Range of motion (ROM) assessments and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and functional limitations were used to evaluate mobility. Results: Joint degeneration was significantly higher in obese individuals, 60% showed joint space narrowing, 68% showed osteophyte formation, and 55% showed subchondral sclerosis (p < 0.001). Knee flexion, hip abduction, and ankle dorsiflexion were significantly reduced in the obese group by 18, 22, and 25%, respectively (p < 0.01). Obese participants had markedly higher WOMAC scores for pain (p < 0.001) and stiffness (p < 0.001) and lesser functional impairment (p < 0.001). Conclusion: obesity has a great negative effect on joint health, mobility, and functional capacity. Early weight management strategies, physiotherapy, and lifestyle modification are needed to avoid musculoskeletal complications of obesity. To decrease the burden of joint disorders, public health policies should focus on obesity prevention. Keywords: Obesity, Joint Integrity, Mobility Impairment, Osteoarthritis, Range of Motion, Musculoskeletal Disorders, Adipokines, Radiographic Assessment.